Community Social Capital and Firm Performance - Rahmawati, Fitriana; Rofiq, Ainur; Wijayanti, Risna (Journal of International Conference Proceedings, 2021)
This study aims to contribute to the social capital theory. This goal is achieved through determine the relationship between social capital and firm performance. It is carried out because SME's have limited access to resources. SME's need other alternatives to sustain their business. Small entrepreneurs feel the need to focus more on their internal resources. The development of the theory of social capital is important. In contrast to most previous studies, this research uses qualitative study research methods. To obtain the data, in-depth interviews with key informants were conducted. The finding shows that social capital consists of reciprocity, trust, network, and norms. This study also provides evidence that social capital plays a pivotal role in SME performance. Small entrepreneurs get various benefits after joining the group. In addition, social capital can help empower ordinary housewives to become small-scale entrepreneurs. In conclusion, strong social capital can improve business performance, thereby encouraging the economy to grow. The results of this research can be used as consideration for business entities to strengthen their business performance. More than that, this research is also used as a guide in determining strategic SME development policies for government. This research also contributes to the development of strategic management theory.